Aligned nematic elastomer
Patent Information
- Application Number
- JP2024059200
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-10-19
- Filing Date
- 2024-04-01
- Publication Date
- 2025-02-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There is a lack of synthetic molecular auxetic materials with negative Poisson's ratio, which exhibit unusual deformation behavior, limiting their application in various fields such as aerospace, automotive, and biomedical applications.
Development of self-assembled nematic elastomers with mechanical Fredericks transition (MFT) that exhibit auxetic properties, utilizing a monodomain liquid crystal elastomer comprising a polymer component, liquid crystal mesogen component, and crosslinker component, with specific chemical compositions and orientation techniques to achieve MFT.
The resulting materials demonstrate improved impact absorbance and shear performance, enabling applications in aerospace, automotive, protection, sports, and biomedical fields, as well as in medical devices and personal protective equipment, due to their auxetic properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the use of oriented nematic elastomers, and in particular their use in forming materials with auxetic properties (that is, they expand laterally when stretched lengthwise). [Background technology]
[0002] In conventional materials, when a material is stretched, it simultaneously becomes thinner in cross section. Similarly, when a conventional material is compressed, the material expands laterally. These conventionally behaving materials have a positive Poisson's ratio, where the Poisson's ratio is described as the negative ratio of the proportional decrease in transverse measurements to the proportional increase in length in a sample of the material that is stretched elastically. On the other hand, materials with auxetic properties have a negative Poisson's ratio. When stretched, the material becomes thicker in one or both directions perpendicular to the applied force. Auxetic materials are of particular interest due to this unusual behavior under deformation. Although auxetic materials exist in nature, such as some materials and many cubic elemental metals, synthetic auxetic materials were only developed in the 1980s. Macroscopic auxetic behavior has been exploited in several applications from sportswear to space travel. The design and synthesis of molecular auxetic materials is a particularly exciting prospect. However, synthetic molecular auxetic materials have yet to be developed to date.
[0003] Liquid crystals have long-range order, and by varying the components that give them their desired properties, the physical properties of the resulting material can be fine-tuned. It has therefore been suggested that liquid crystal polymers exhibiting auxetic properties could be developed. However, to date, no such materials have been reported. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Phys.Rev.Lett.,1993,71(18),2947 [Non-Patent Document 2] J. Phys.,II France,1997,7,1337 [Non-Patent Document 3] Mol.Cryst.Liq.Cryst.,1997,299,181 Summary of the Invention [Means for solving the problem]
[0005] The applicant has surprisingly developed a self-assembled nematic material that has auxetic properties. In a first embodiment, there is provided the use of an oriented nematic elastomer to form a material with auxetic properties, the oriented nematic material having a Mechanical Freedericks Transition (MFT).
[0006] Surprisingly, it has been found that by forming oriented nematic elastomers that exhibit MFT, the resulting materials have auxetic properties and are therefore used in a wide range of novel applications. Because the materials have auxetic properties, they demonstrate improved shock absorbency and shear performance. These properties are useful in multiple applications, for example in aerospace, automotive, protective and sports applications, as well as in applications in the biomedical field where materials with auxetic properties can be used to mimic biological systems. Uses are anticipated in medical devices, such as stents and valves and vasodilators, where controlled expansion and contraction with external stimuli is important, and in prosthetic materials and surgical implants, where response to external pressure is particularly useful. The materials can also be used in medical connections, such as sutures and anchors, or for controlled release of active pharmaceutical ingredients by controlled contraction or expansion.
[0007] Materials exhibiting auxetic properties may also find application in piezoelectric sensors and actuators, and in micro- and nano-mechanical and electromechanical devices. Other potential uses include composites where materials exhibiting auxetic properties can act as reinforcements, or in personal protective clothing such as crash helmets, bulletproof vests, and sportswear where expansion in response to an external force is clearly desirable.
[0008] The mechanical Freedericks transition is defined as a deformation mode of oriented elastomers in which the director in the elastomer rotates sharply at a critical strain and reorients parallel to the stress axis at a critical elongation. Materials exhibiting this property were first described by Mitchell et al. (Mitchell, GR, Davis, FJ and Guo, W., Phys. Rev. Lett., 1993, 71(18), 2947) and Roberts et al. (Roberts, PMS, Mitchell, GR and Davis, FJ, J. Phys, II France, 1997, 7, 1337 and Roberts, PMS, Mitchell, GR, Davis, FJ and Pople, JA, Mol. Cryst. Liq. Cryst., 1997, 299, 181). MFT is often described in analogy with the well-known electric (or magnetic) field Frederickss transition (EFT) that occurs in low molar mass nematic display devices. In EFT, the director reorients sharply beyond a well-defined critical magnetic field (or voltage), becoming more aligned with respect to the electric field as the magnetic field amplitude increases. The EFT threshold is theoretically discontinuous, but is known to be softened when ideal LC monodomains aligned exactly parallel or perpendicular to the substrate are not achieved in practice. Nevertheless, the threshold is sharp and well-defined. The sharp rotation of the director seen in MFT differs from the director rotation response of oriented elastomers deforming by an alternative deformation mode, semi-soft elasticity (SSE). In the semi-soft elastic case, the director rotates relatively gradually across a plateau-like region of the tensile loading curve. A theoretical plot demonstrating the SSE transition is shown in Figure 1. The director rotates gradually across region II.
[0009] The mechanical Freedericks transition can be measured by applying a stress in a direction perpendicular or near perpendicular to the oriented director in the sample and tracking the orientation of the director, for example by using polarized light microscopy.
[0010] Such a method is - mounting a strip of elastomer in the clamps of opposing actuators and placing the strip between crossed polarizers; - gradually applying strain by elongating the strip in a direction perpendicular to the initial director orientation at up to 5% of the initial length per minute; - at each elongation increment, taking a series of measurements of the transmitted light intensity (the intensity of light transmitted through the polarizer, the strip and the analyzer) with the polarizer and the analyzer rotated relative to the strip by 10 degrees between each measurement; - c, To determine the angle of the director with respect to the direction of the applied stress, Eq.
number
[0011] The oriented nematic elastomer preferably comprises a monodomain liquid crystal elastomer, more preferably the oriented nematic elastomer is a monodomain liquid crystal elastomer.
[0012] By "monodomain" herein is meant that the orientation of the director of the elastomer is macroscopically oriented in the sample. Monodomain orientation across a sample can be measured, for example, by polarized light microscopy, where a macroscopic sample is characterized by uniform birefringence when viewed between crossed polarizers.
[0013] Preferably, the oriented nematic elastomer is a monodomain liquid crystal elastomer comprising a polymer component, a liquid crystal mesogen component, and a crosslinker component, wherein the liquid crystal mesogen component is physically linked to the polymer component.
[0014] Preferably, the liquid crystal mesogenic component is physically linked to the polymer component via a flexible spacer.
[0015] Preferably, the flexible spacer is C2 to C 10 Alkylene group, preferably linear C2-C 10 The flexible spacer preferably comprises an alkylene group, more preferably a linear C3-C7 alkylene group, and most preferably a linear C3 or C6 alkylene group. For example, the flexible spacer may comprise an ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene group.
[0016] The liquid crystal mesogen component of the liquid crystal elastomer may include any suitable nematic mesogen.
[0017] Preferably, the liquid crystal mesogenic component comprises a liquid crystal core component selected from the group consisting of aromatic rings, aliphatic rings, polycyclic aromatic rings, polycyclic aliphatic rings, phenyls, biphenyls, benzenes, and combinations thereof.
[0018] Preferably, the liquid crystal core component contains multiple aromatic and / or aliphatic rings.
[0019] Preferably, the liquid crystal core component is a system of: [ka] wherein R and R' are each independently selected from the group consisting of alkyl, alkoxy, halide, -NO2 or -CN, where the alkyl and alkoxy groups may be divalent when forming part of a linking group connecting the liquid crystal core to a polymer component, and X and Y are each independently selected from the group consisting of -CH=CH-, -C≡C-, -CH=N-, -N=N- or -C(O)O-. is selected from one or more of the following:
[0020] Preferably, the liquid crystal core component contains at least two phenyl groups.
[0021] The phenyl group can be optionally substituted with any suitable functional group.
[0022] Preferably, at least one of X or Y is -C(O)O-, or X or Y is absent.
[0023] Preferably, the liquid crystal core component is selected from 4-cyano-biphenyl-4'-yloxy, 4-oxyphenyl 4-methoxybenzoate or 4-oxyphenyl 4-(trans-4-propylcyclohexyl)benzoate groups.
[0024] In certain embodiments, the liquid crystal mesogenic components are present as part of the side chains of the polymer component, ie, the liquid crystal mesogenic components are pendant groups extending from the main chain of the polymer component.
[0025] In certain embodiments, the liquid crystal mesogenic component is present as part of the backbone of the polymer component.
[0026] The liquid crystal mesogenic components may form part of both the side chains and the main chain of the polymer component.
[0027] The crosslinker component preferably comprises a difunctional monomer having the same functionality as the polymer component.
[0028] Preferably, the crosslinker component also comprises a mesogen component. Preferably, the mesogen component is a compound selected from the group consisting of the following systems: [ka] wherein R and R' are each independently selected from the group consisting of alkyl, alkoxy, halide, -NO2 or -CN, where the alkyl and alkoxy groups may be divalent when forming part of a linking group connecting the liquid crystal core to a polymer component, and X and Y are each independently selected from -CH=CH-, -C≡C-, -CH=N-, -N=N- or -C(O)O-. The liquid crystal core component is selected from one or more of the following:
[0029] Preferably, the liquid crystal core component comprises at least three phenyl groups. Preferably, at least one of X or Y is -C(O)O-.
[0030] The phenyl group may be optionally substituted with any suitable functional group. Preferably, the phenyl group is optionally substituted with one or more C1-C3 alkyl groups, most preferably one or more methyl groups.
[0031] Preferably, the liquid crystal core component comprises an optionally substituted bis-oxybenzoyloxybenzene group, most preferably a bis-oxybenzoyloxy-2-methylbenzene group.
[0032] The polymer component can be any suitable polymer component. Preferably, the polymer component comprises an acrylate polymer, a vinyl polymer, a siloxane polymer, a thiol-based polymer, an amine-based polymer, or an epoxide-based polymer. Most preferably, the polymer component comprises an acrylate polymer.
[0033] In certain embodiments, the polymer component is formed from both mesogenic and non-mesogenic components.
[0034] Preferably, the mesogenic component is formed from a mesogenic monomer which comprises a monomer unit linked to a liquid crystal core component.
[0035] The non-mesogenic component may be a Tg lowering component. In a preferred embodiment, the elastomer for use according to the first embodiment of the invention has a Tg below room temperature (25° C.).
[0036] In a preferred embodiment, the Tg lowering component is a monomer unit and a pendant mid-chain (C2-C 12 ) a straight or branched alkyl group.
[0037] In a particularly preferred embodiment, the polymer component comprises an acrylate polymer and the Tg lowering component comprises ethylhexyl acrylate.
[0038] In a preferred embodiment of the invention, the polymer component comprises a polyacrylate, the liquid crystal core component is a 4-cyano-biphenyl-4'-yloxy component, and the crosslinker component comprises a bis-oxybenzoyloxy-2 methylbenzene-containing component.
[0039] The elastomer for use according to the first embodiment is preferably formed by polymerizing a mixture comprising a mesogenic monomer, a cross-linking component, and an initiator. The mixture may further comprise a non-mesogenic monomer to modify the properties of the final elastomer, for example to reduce the Tg of the final elastomer. The mixture may also further comprise a non-reactive mesogenic component to broaden the nematic phase range prior to polymerization. In a preferred embodiment, the cross-linking component also comprises a mesogenic component.
[0040] Preferably, the mesogenic monomer comprises about 5-50 mol % of the monomer mixture before polymerization, more preferably about 10-30 mol %, most preferably about 15 mol %. In the final elastomer, the proportion of material derived from the mesogenic monomer is preferably about 20-70 mol %, most preferably about 30-60 mol %.
[0041] Preferably, the crosslinker component comprises about 1-20 mol % of the monomer mixture prior to polymerization, more preferably about 3-10 mol %, and most preferably about 3-8 mol %. In the final elastomer, the proportion of material derived from the crosslinker component is preferably about 5-20 mol %, and most preferably about 8-17 mol %.
[0042] Preferably, at least 10% of the crosslinker components comprise a mesogenic component, preferably at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90% or at least 95% of the crosslinker components comprise a mesogenic component.
[0043] The initiator selected depends on the polymer used and can be any suitable initiator. However, when the polymer is a polyacrylate, the initiator is preferably a photoinitiator. Possible photoinitiators are well known to those skilled in the art and include benzoin ethers, benzil ketals, alpha-dialkoxyacetophenones, alpha-hydroxyalkylphenones, acylphosphine oxides, benzophenones and thioxanthones. Preferably, the photoinitiator is methylbenzoyl formate. Preferably, the initiator is present in an amount of approximately 1.5 mol% of the monomer mixture.
[0044] If non-mesogenic monomers are present in the monomer mixture, they preferably comprise about 10-40 mol % of the monomer mixture, more preferably about 15-30 mol %, most preferably about 15-20 mol %. In the final elastomer, the proportion of material derived from non-mesogenic monomers, if present, is preferably about 20-60 mol %, most preferably about 35-50 mol %.
[0045] When the non-reactive mesogen is present in the monomer mixture, it preferably comprises about 10-70 mol %, more preferably about 20-60 mol % or 30-60 mol %, and most preferably about 55 mol % of the monomer mixture. In a preferred embodiment, the non-reactive mesogen is 4-cyano-4'-hexyloxybiphenyl.
[0046] In a preferred embodiment, the mesogenic monomer is 6-(4-cyano-biphenyl-4'-yloxy)hexyl acrylate, 4-methoxybenzoic acid 4-(6-acryloyloxy-hexyloxy)phenyl ester or 4-{6-(acryloyloxy)hexyloxy}phenyl 4-(trans-4-propylcyclohexyl)benzoate, the crosslinker component is 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene or 1,4-bis-[4-(3-acryloyloxypropyloxy)benzoyloxy]-2-methylbenzene, the non-mesogenic monomer is 2-ethylhexyl acrylate and, if present, the non-reactive mesogen is 4-cyano-4'-hexyloxybiphenyl.
[0047] In a preferred embodiment, the mesogenic monomer is 6-(4-cyano-biphenyl-4'-yloxy)hexyl acrylate, the crosslinker component is 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, the non-mesogenic monomer is 2-ethylhexyl acrylate, and the non-reactive mesogen, if present, is 4-cyano-4'-hexyloxybiphenyl, or the mesogenic monomers are 4-methoxybenzoic acid 4-(6-acryloyloxy-hexyloxy)phenyl ester and 4-{6-(acryloyloxy)hexyloxy}phenyl 4-(trans-4-propylcyclohexyl)benzoate, and the crosslinker component is 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene. The crosslinker component is 4-bis-[4-(3-acryloyloxypropyloxy)benzoyloxy]-2-methylbenzene, the non-mesogenic monomer is 2-ethylhexyl acrylate, and the non-reactive mesogen, if present, is 4-cyano-4'-hexyloxybiphenyl; or the mesogenic monomers are 4-methoxybenzoic acid 4-(6-acryloyloxy-hexyloxy)phenyl ester and 4-{6-(acryloyloxy)hexyloxy}phenyl 4-(trans-4-propylcyclohexyl)benzoate, the crosslinker component is 4-bis-[4-(3-acryloyloxypropyloxy)benzoyloxy]-2-methylbenzene, the non-mesogenic monomer is 2-ethylhexyl acrylate, and the non-reactive mesogen, if present, is 4-cyano-4'-hexyloxybiphenyl.
[0048] According to a further embodiment of the invention there is provided a method of producing an oriented nematic elastomer for use according to the first embodiment of the invention, comprising the steps of: a) applying an orientation means to a substrate; b) applying liquid crystal elastomer components to a substrate and allowing them to form an oriented nematic phase; c) curing the liquid crystal elastomer component to form an oriented nematic elastomer. A method is provided that includes:
[0049] There are various techniques for orienting mesogenic compositions. For example, techniques such as applying a magnetic field, mechanical brushing, flow, applying an electric field, applying a thermal gradient, or providing one or more alignment layers exist to create a monodomain during synthesis. The monomer solution can also be heated, cooled, or exposed to other environmental factors to affect the synthesis of the monomer mixture into an oriented state.
[0050] Preferably, the orienting means is an orienting force that is applied by brushing the substrate, preferably to apply a static force to the substrate.
[0051] When the cross-linking component comprises a mesogenic component and can therefore also be considered a mesogenic monomer, the ratio of mesogenic to non-mesogenic monomers in the final elastomer is preferably from 2:1 to 1:1.
[0052] Embodiments of the invention will now be described with reference to the accompanying examples and with reference to the drawings. [Brief description of the drawings]
[0053] [Figure 1] 1 shows a theoretical plot of elongation versus stress for a material exhibiting an SSE transition. [Figure 2a] FIG. 1 shows plots of fractional thickness versus elongation and Poisson's ratio versus elongation for the material of Example 1. Values of Poisson's ratio below zero indicate auxetic behavior. [Figure 2b] 1 shows plots of fractional thickness versus elongation and Poisson's ratio versus elongation for the material of Example 2. Values of Poisson's ratio below zero indicate auxetic behavior. [Figure 2c] Figure 1 shows plots of fractional thickness versus elongation and Poisson's ratio versus elongation for the material of Example 3. Values of Poisson's ratio below zero indicate auxetic behavior. [Figure 2d] Figure 1 shows plots of fractional thickness versus elongation and Poisson's ratio versus elongation for the material of Example 4. Values of Poisson's ratio below zero indicate auxetic behavior. [Figure 3a]1 shows a tensile load curve and a plot of director angle response versus elongation for the material of Example 1. [Figure 3b] 1 shows a tensile load curve and a plot of director angle response versus elongation for the material of Example 2. [Figure 3c] 1 shows a tensile load curve and a plot of director angle response versus elongation for the material of Example 3. [Figure 3d] 1 shows a tensile load curve and a plot of director angle response versus elongation for the material of Example 4. [Figure 4] 1 shows plots of fractional change versus strain for the material of Example 1 at various temperatures and various elongations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] Elastomer Synthesis The oriented nematic elastomers for use according to the invention are the following materials: 2-Ethylhexyl acrylate (EHA), 6-(4-cyano-biphenyl-4'-yloxy)hexyl acrylate (A6OCB), 4-Methoxybenzoic acid 4-(6-acryloyloxy-hexyloxy)phenyl ester (M1), 4-{6-(acryloyloxy)hexyloxy}phenyl 4-(trans-4-propylcyclohexyl)benzoate (M2), 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (RM82), 1,4-bis-[4-(3-acryloyloxypropyloxy)benzoyloxy]-2-methylbenzene (RM257), 4-cyano-4'-hexyloxybiphenyl (6OCB), and Methylbenzoylformate (MBF) It was synthesized as follows:
[0055] Elastomers for use according to the invention were prepared using the following starting compositions:
[0056] [Table 1]
[0057] The dry material was weighed into a 4 ml sample vial using a balance with 0.3 mg accuracy. The mixture was then heated to 100° C. and stirred at 60 rpm for 5 minutes. The liquid material was added and the vial was placed on a separate stir plate held at 40° C. and stirred at 60 rpm for an additional 5 minutes.
[0058] The mixture is then filled with the isotopic phase at 40 °C by capillary action into the previously prepared cell and left to cool to ambient temperature for approximately half an hour to allow the nematic phase to form by alignment with the rubbing direction. Once aligned, the cell is exposed to a low intensity UV fluorescent light source (2.5 mW cm) for 2 hours. -2 The LCE film was cured under a 300 MPa (1000 MPa) strength of 1000 MPa (1000 MPa). Upon separation from the cell, the film was washed in dichloromethane (DCM) by slow, stepwise addition of DCM to a concentration of approximately 30%. The solvent was exchanged several times to ensure all waste was removed, after which the LCE film was deswollen by stepwise addition of methanol. The film was allowed to dry thoroughly overnight before testing.
[0059] The auxetic properties of the four materials are demonstrated in Figures 2a, 2b, 2c, and 2d, respectively, which show that the materials have negative Poisson's ratios. Beyond an elongation of approximately 1.8 in Figure 2a, approximately 1.5 in Figure 2b, approximately 1.6 in Figure 2c, and approximately 1.6 in Figure 2d, the fractional thickness of the material increases with increasing elongation. Figures 3a, 3b, 3c, and 3d demonstrate that the materials each have an MFT. In Figure 3a, a sharp change in the director angle is seen at a strain of approximately 2.1. In Figure 3b, a sharp change in the director angle is seen at an x-strain of approximately 1.9. In Figure 3c, a sharp change in the director angle is seen at an x-strain of approximately 1.9. In Figure 3d, a sharp change in the director angle is seen at an x-strain of approximately 1.9.
Claims
1. Use of an oriented nematic elastomer to form a material having auxetic properties, the oriented nematic material having a mechanical Freedericks transition, the oriented nematic elastomer comprises a monodomain liquid crystal elastomer; The monodomain liquid crystal elastomer comprises a polymer component, a liquid crystal mesogen component, and a crosslinker component; the liquid crystal mesogenic component is physically linked to the polymer component via a flexible spacer; The flexible spacer is an oriented nematic elastomer comprising a C 2 -C 10 alkylene group.
2. 2. The use of an oriented nematic elastomer according to claim 1, wherein the material having auxetic properties is used in a medical device or biomedical application.
3. 2. Use of an oriented nematic elastomer according to claim 1, wherein the material with auxetic properties is used in a piezoelectric sensor or actuator or a micro- or nano-mechanical or electromechanical device.
4. 2. Use of the oriented nematic elastomer according to claim 1, wherein the material with auxetic properties is used in composites as reinforcement or in personal protective clothing.
5. 2. The use of an oriented nematic elastomer according to claim 1, wherein the liquid crystal mesogenic component comprises a liquid crystal core component selected from the group consisting of aromatic rings, aliphatic rings, polycyclic aromatic rings, polycyclic aliphatic rings, phenyls, biphenyls, benzenes and combinations thereof.
6. The liquid crystal core component is: 【Chemistry 1】 (wherein R and R′ are alkyl, alkoxy, halide, —NO 2 or -CN, where the alkyl and alkoxy groups may be divalent when forming part of a linking group connecting the liquid crystal core component to the polymer component, and X and Y are independently selected from the group consisting of -CH=CH-, -C≡C-, -CH=N-, -N=N- or -C(O)O-.
6. Use of an oriented nematic elastomer according to claim 5, selected from one or more of the following:
7. 2. Use of an oriented nematic elastomer according to claim 1, wherein the polymer component is formed from both mesogenic and non-mesogenic components.
8. The use of an oriented nematic elastomer according to claim 7, wherein the polymeric component comprises an acrylate polymer and the non-mesogenic component comprises 2-ethylhexyl acrylate.
9. The use of an oriented nematic elastomer according to claim 1 , wherein the crosslinker component comprises a mesogenic component.
10. 8. Use of an oriented nematic elastomer according to claim 7, wherein the mesogenic component is 6-(4-cyano-biphenyl-4'-yloxy)hexyl acrylate, the crosslinker component is 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and the non-mesogenic component is 2-ethylhexyl acrylate.
11. A method for producing an oriented nematic elastomer for use according to any one of claims 1 to 10, comprising the steps of: a) applying an orientation means to a substrate; b) applying liquid crystal elastomer components to said substrate and allowing them to form an oriented nematic phase; c) curing the liquid crystal elastomer component to form an oriented nematic elastomer. A method for producing an oriented nematic elastomer comprising:
12. 12. The method of claim 11, wherein the orienting means is an orienting force applied by brushing the substrate.